Micro-display blue light perovskite light-emitting diode and preparation method thereof

CN122995413APending Publication Date: 2026-10-27HBR ELECTRONICS (JIANGSU) CO LTD
2 Cites 0 Cited by

Patent Information

Application Number
CN202610995816.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-06
Publication Date
2026-10-27

Smart Images

  • Figure CN122995413A_ABST
    Figure CN122995413A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of perovskite light-emitting diodes, and discloses a micro-display blue light perovskite light-emitting diode and a preparation method thereof. The light-emitting diode comprises a substrate, an ITO anode, a hole injection layer, a composite hole transport layer, a composite interface passivation layer, a quasi-two-dimensional blue light perovskite light-emitting layer, a composite electron transport layer, an electron injection layer and a metal cathode which are sequentially arranged. The preparation method comprises the following steps: sequentially preparing the hole injection layer, the composite hole transport layer and the composite interface passivation layer; coating a quasi-two-dimensional blue light perovskite precursor solution containing ammonium formate to form a wet film, and performing two-stage annealing to form the light-emitting layer; and then preparing the composite electron transport layer, the electron injection layer and the metal cathode. The application is used for improving the problem that the quasi-two-dimensional blue light perovskite light-emitting layer defect adjustment and carrier transfer are difficult to be considered simultaneously.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of perovskite light-emitting diode technology, and more particularly to a micro-display blue perovskite light-emitting diode and its fabrication method. Background Technology

[0002] Perovskite light-emitting diodes (LEDs) have been used in research on high color gamut displays, near-eye displays, and micro-display devices. Among them, red, green, and near-infrared perovskite LEDs have achieved high external quantum efficiencies, while the performance of blue LED devices is still limited by defects in the emitting layer. During the crystallization process, blue perovskite emitting layers are prone to forming halogen vacancies, grain boundary defects, and interface defects. These defects can cause non-radiative recombination, thereby reducing the electroluminescence efficiency and continuous illumination stability of the device.

[0003] To address the issue of numerous defects in blue perovskite light-emitting layers, existing technologies have proposed corresponding improvement solutions. For example, Chinese patent CN111048690A discloses a blue perovskite film and a blue perovskite light-emitting diode, which prepares the blue perovskite film using components such as PEABr, NPABr2, CsBr, and PbBr2. Chinese patent CN111916572A discloses a perovskite light-emitting diode with mixed cations and mixed anions and its preparation method. By controlling the composition of mixed cations and mixed anions, the perovskite cation vacancies and anion vacancies are reduced, the defect state density is lowered, and nonradiative recombination caused by vacancy defects is suppressed. The above-mentioned existing technologies mainly improve the defect state of the blue perovskite light-emitting layer from aspects such as component control, vacancy defect passivation, or the introduction of organic passivating agents.

[0004] Quasi-two-dimensional blue perovskite light-emitting diodes typically require the introduction of a certain amount of organic spacer cations to enhance the quantum confinement effect and adjust the material band gap, thereby obtaining shorter wavelength blue light emission. To reduce grain boundary defects, halogen vacancies, or interface defects, organic passivators are further introduced for defect repair. However, Zhenwei Ren et al. pointed out in "High-Performance Blue Quasi-2D Perovskite Light-Emitting Diodes via Balanced Carrier Confinement and Transfer" published in Nano-Micro Letters that blue quasi-two-dimensional perovskites require a large amount of insulating organic spacer cations to adjust the band gap, but these organic spacer cations will hinder carrier transfer. Furthermore, the insulating carbon chains of traditional long-chain passivators usually do not participate in effective charge transport, and increasing their content will increase the resistance to carrier transfer within the light-emitting layer or injection at the functional layer interface. Summary of the Invention

[0005] The technical problem to be solved by this invention is that the nucleation and crystallization processes of existing micro-display blue perovskite light-emitting layers are difficult to coordinate within the micron-level pixel region, and the addition of organic passivation components can easily hinder carrier transfer, making it difficult to balance the device's luminous efficiency and continuous illumination stability. To address this, we propose a micro-display blue perovskite light-emitting diode and its fabrication method.

[0006] The present invention provides a micro-display blue perovskite light-emitting diode, comprising a substrate and an ITO anode disposed on one side of the substrate; along the direction away from the substrate, a hole injection layer, a composite hole transport layer, a composite interface passivation layer, a quasi-two-dimensional blue perovskite light-emitting layer, a composite electron transport layer, an electron injection layer and a metal cathode are sequentially stacked on one side of the ITO anode.

[0007] Preferably, the substrate is selected from a glass substrate, a quartz substrate, a silicon-based substrate, or a flexible transparent substrate.

[0008] Preferably, the ITO anode is an ITO transparent conductive film with a thickness of 120-150 nm and a sheet resistance of 8-15 Ω / sq.

[0009] Preferably, the hole injection layer is a PEDOT:PSS layer with a thickness of 25-35nm.

[0010] Preferably, the composite hole transport layer includes a TFB layer and a PTAA layer, wherein the thickness of the TFB layer is 15-25 nm and the thickness of the PTAA layer is 20-30 nm.

[0011] Preferably, the composite interface passivation layer is formed by compounding 3-aminopropyltriethoxysilane and phenylethylamine bromide (PEABr), wherein the mass ratio of 3-aminopropyltriethoxysilane to PEABr is 1.5:1-3:1, preferably 2:1; and the thickness of the composite interface passivation layer is 2-8 nm, preferably 3-5 nm.

[0012] Preferably, the raw materials for preparing the quasi-two-dimensional blue perovskite luminescent layer include CsBr, PbBr2, PbCl2, PEABr, tetramethylammonium bromide (TMABr), LiBr, MgBr2 and ammonium formate; wherein the molar ratio of PEABr to TMABr is 1:(0.3-1.2), preferably 1:0.6.

[0013] Preferably, the molar ratio of Br to Cl in the raw materials is 7:3-9:1, and more preferably 8:2.

[0014] Preferably, LiBr and MgBr2 are used as metal bromide dopants; based on a total molar amount of 100 mol% for PbBr2 and PbCl2, the total molar amount of LiBr and MgBr2 is 0.5-5 mol%, preferably 1.5-3 mol.

[0015] Preferably, based on a total molar amount of PbBr2 and PbCl2 of 100 mol%, the amount of ammonium formate added is 0.2-3.0 mol%, preferably 0.5-1.5 mol.

[0016] Preferably, the quasi-two-dimensional blue light perovskite precursor solution is dissolved in a mixed solvent of DMF and DMSO, with a volume ratio of DMF to DMSO of 4:1 and a solid content of 12-18 mg / mL.

[0017] Preferably, the composite electron transport layer is a blend of PO-T2T and TPBi, with a mass ratio of PO-T2T to TPBi of 1:1.2-1.2:1, preferably 1:1; the thickness of the composite electron transport layer is 25-35 nm.

[0018] Preferably, the electron injection layer is a LiF layer with a thickness of 0.8-1.2 nm.

[0019] Preferably, the metal cathode is disposed on the side of the electron injection layer away from the quasi-two-dimensional blue perovskite emitting layer, and the metal cathode is an Ag layer with a thickness of 90-110 nm.

[0020] In the above structure, the ITO anode, PEDOT:PSS layer, TFB / PTAA composite hole transport layer, PO-T2T / TPBi composite electron transport layer, LiF layer and Ag cathode constitute carrier injection and transport channels, which are used to inject holes and electrons into the quasi-two-dimensional blue perovskite light-emitting layer from the anode side and the cathode side, respectively.

[0021] CsBr, PbBr2, and PbCl2 are used to form the cesium-based bromochlorine mixed halide perovskite framework, and the Br / Cl ratio is used to adjust the band gap of the luminescent layer. PEABr and TMABr, as organic ammonium components, are used to form a quasi-two-dimensional structure and regulate the crystallization process. Their dosage is limited by the ratio to reduce the influence of excessive organic components on carrier transfer.

[0022] LiBr and MgBr2 are used to regulate halogen vacancies and grain boundary defects formed during the crystallization process of the luminescent layer; the 3-aminopropyltriethoxysilane / PEABr composite interface passivation layer is used to reduce interface defects between the composite hole transport layer and the quasi-two-dimensional blue perovskite luminescent layer.

[0023] Ammonium formate can participate in precursor coordination and crystallization regulation during the initial crystallization process of quasi-two-dimensional blue perovskite wet films, and reduce its residual amount in the light-emitting layer after subsequent annealing, thereby reducing the adverse effects of additional organic residues on carrier transfer.

[0024] like Figure 1 As shown, the present invention also provides a method for fabricating a micro-display blue perovskite light-emitting diode, comprising the following steps:

[0025] S1: The substrate with multiple electrically isolated ITO pixel electrodes is cleaned and treated with ultraviolet ozone to prepare a hole injection layer on the surface of the multiple ITO pixel electrodes.

[0026] S2: A TFB layer and a PTAA layer are sequentially prepared on the hole injection layer to form a composite hole transport layer;

[0027] S3: Prepare a composite interface passivation layer on the composite hole transport layer;

[0028] S4: Prepare a quasi-two-dimensional blue light perovskite precursor solution containing ammonium formate;

[0029] S5: A pixel isolation barrier is formed on the surface of the composite interface passivation layer, and the pixel isolation barrier forms a plurality of pixel openings that correspond one-to-one with the ITO pixel electrodes; the quasi-two-dimensional blue light perovskite precursor liquid is coated in the plurality of pixel openings to form perovskite wet films spaced apart from each other.

[0030] S6: The perovskite wet film is subjected to a two-stage annealing process. The first stage annealing temperature is 50-70℃ and the time is 1-3 min. The second stage annealing temperature is 85-100℃ and the time is 5-10 min to obtain a quasi-two-dimensional blue light perovskite emitting layer.

[0031] S7: A composite electron transport layer, an electron injection layer, and a metal cathode are sequentially fabricated on multiple quasi-two-dimensional blue light-emitting perovskite layers to form multiple blue light-emitting units disposed on the same substrate.

[0032] Preferably, in step S1, the hole injection layer is a PEDOT:PSS layer; the hole injection layer is prepared using a PEDOT:PSS aqueous dispersion with a solid content of 1.0-2.0 wt%. The PEDOT:PSS aqueous dispersion is filtered through an aqueous filter membrane with a pore size of 0.22-0.45 μm, and then spin-coated onto the surface of the ITO pixel electrode at a speed of 3000-5000 r / min for 30-60 s. Subsequently, it is heat-treated at 130-150℃ for 15-25 min to form a PEDOT:PSS hole injection layer with a thickness of 25-35 nm.

[0033] Preferably, in step S2, TFB is dissolved in anhydrous chlorobenzene to prepare a TFB solution with a concentration of 8 mg / mL. The TFB solution is spin-coated onto the surface of the hole injection layer at a speed of 3000 r / min for 30 s, followed by heat treatment at 150°C for 20 min to form a TFB layer with a thickness of 20 nm. PTAA is dissolved in anhydrous toluene to prepare a PTAA solution with a concentration of 5 mg / mL. The PTAA solution is spin-coated onto the surface of the TFB layer at a speed of 3000 r / min for 30 s, followed by heat treatment at 100°C for 10 min to form a PTAA layer with a thickness of 25 nm.

[0034] Preferably, in step S3, 3-aminopropyltriethoxysilane and PEABr are added to isopropanol at a mass ratio of 1.5:1-3:1 and mixed evenly to obtain a composite interface passivation solution with a total concentration of 0.5-2.0 mg / mL. The composite interface passivation solution is spin-coated onto the surface of the composite hole transport layer at a rotation speed of 2000-4000 r / min for 20-40 s, and then cured at 50-80℃ for 5-15 min to form a composite interface passivation layer with a thickness of 2-8 nm.

[0035] Preferably, in step S5, the coating method is spin coating or inkjet printing.

[0036] Preferably, when using spin coating, the substrate preheating temperature is 55-70℃, preferably 60℃; the process includes a first stage of low-speed homogenization and a second stage of high-speed film formation. The first stage has a rotation speed of 800-1200 r / min and a time of 8-12 s; the second stage has a rotation speed of 2800-3500 r / min and a time of 30-45 s; and 0.08-0.12 mL of anhydrous chlorobenzene is added as an anti-solvent during the 22nd-28th s of the second stage spin coating.

[0037] Preferably, when using inkjet printing, a pixel isolation barrier is formed on the surface of the composite interface passivation layer to form a pixel opening, and the quasi-two-dimensional blue light perovskite precursor liquid is printed into the pixel opening; the substrate temperature is 45-55℃ during printing, and the relative humidity of the printing environment is less than 18%.

[0038] Preferably, the thickness of the quasi-two-dimensional blue perovskite emitting layer is 30-60 nm, and more preferably 40-50 nm.

[0039] Preferably, in step S7, the composite electron transport layer, electron injection layer, and metal cathode are formed by vacuum evaporation.

[0040] The present invention also provides the application of the blue perovskite light-emitting diode in microdisplay devices.

[0041] The blue perovskite light-emitting diode includes multiple blue light-emitting units spaced apart on the same substrate. Each blue light-emitting unit can serve as a blue light-emitting pixel or a blue sub-pixel in a microdisplay device to form a monochrome blue light microdisplay device, or it can be combined with red and green light-emitting pixels to form a full-color microdisplay device. The microdisplay device can be applied to near-eye displays, head-mounted displays, electronic viewfinders, micro-projection devices, or wearable display devices.

[0042] The beneficial effects of this invention are as follows:

[0043] This invention introduces ammonium formate into the quasi-two-dimensional blue light perovskite precursor solution and uses a two-stage annealing process to enable ammonium formate to participate in defect regulation and crystallization control in the early stage of film formation and reduce its residue in the subsequent annealing stage. Compared with directly adding long-chain organic passivating agents, this method can reduce the obstacles to carrier transfer caused by the long-term residue of additional organic components in the light-emitting layer.

[0044] This invention achieves a match between blue light emission, defect modulation, and charge transfer in the quasi-two-dimensional blue perovskite light-emitting layer by combining PEABr / TMABr with organic ammonium components, LiBr / MgBr2 metal bromide doping, Br / Cl mixed halide ratio adjustment, aminosilane-PEABr composite interface passivation layer, and composite carrier transport layer. This is beneficial for improving the electroluminescence efficiency and continuous lighting stability of micro-display blue perovskite light-emitting diodes. Attached Figure Description

[0045] The disclosure of this invention is illustrated with reference to the accompanying drawings. It should be understood that the drawings are for illustrative purposes only and are not intended to limit the scope of protection of this invention. In the drawings:

[0046] Figure 1 This is a flowchart illustrating the fabrication process of the blue perovskite light-emitting diode stack of the present invention;

[0047] Figure 2 This is a graph showing the current density, voltage, and brightness of Embodiment 1 of the present invention;

[0048] Figure 3 This is a comparative example 1 of the present invention, showing the current density, voltage, and brightness curves.

[0049] Figure 4 This is a comparative example 2 of the present invention, showing the current density, voltage, and brightness curves.

[0050] Figure 5 This is a comparative example 3 of the present invention, showing the current density, voltage, and brightness curves.

[0051] Figure 6 The figures show the brightness and EQE curves of Embodiment 1 and Comparative Examples 1-3 of the present invention. Detailed Implementation

[0052] Example 1

[0053] This embodiment provides a method for fabricating a micro-display blue perovskite light-emitting diode, including the following steps:

[0054] S1: A 130nm thick ITO anode glass substrate with a sheet resistance of 10Ω / sq was selected. It was ultrasonically cleaned in deionized water, acetone and isopropanol for 15min each, then dried with nitrogen and treated with ultraviolet ozone for 15min. A PEDOT:PSS aqueous dispersion with a solid content of 1.3–1.7wt% was filtered through a 0.45μm aqueous filter membrane and spin-coated onto the ITO surface at 4000r / min for 40s. Then, it was heat-treated at 140℃ for 20min to obtain a PEDOT:PSS hole injection layer with a thickness of about 30nm.

[0055] S2: Dissolve TFB in anhydrous chlorobenzene to prepare an 8 mg / mL solution. Spin-coat the solution at 3000 r / min for 30 s, then anneal at 150 °C for 20 min to form a 20 nm thick TFB layer. Then, spin-coat a 5 mg / mL anhydrous toluene solution of PTAA onto the TFB layer at the same speed and time, and anneal at 100 °C for 10 min to obtain a 25 nm thick PTAA layer. The TFB layer and the PTAA layer together constitute a composite hole transport layer.

[0056] S3: Add 3-aminopropyltriethoxysilane and PEABr to anhydrous isopropanol at a mass ratio of 2:1 to prepare a composite interface passivation solution with a total concentration of 1.5 mg / mL. Stir at room temperature for 30 min, then spin coat the passivation solution onto the PTAA layer surface at 3000 r / min for 30 s, and cure at 70 °C for 10 min to form a composite interface passivation layer with a thickness of about 4 nm.

[0057] S4: Using DMF and DMSO in a volume ratio of 4:1 as a mixed solvent, 0.1875 mmol of CsBr, 0.1680 mmol of PbBr2, 0.0820 mmol of PbCl2, 0.0781 mmol of PEABr, 0.0469 mmol of TMABr, 0.0025 mmol of LiBr, 0.0025 mmol of MgBr2, and 0.0025 mmol of ammonium formate were dissolved sequentially, and the volume was adjusted to 9.88 mL with the same solvent to obtain a quasi-two-dimensional blue light perovskite precursor solution with a solid content of 15 mg / mL. Among them, the molar ratio of PEABr to TMABr was 1:0.6, and the molar ratio of Br to Cl was 8:2. Based on the total molar amount of PbBr2 and PbCl2 being 100 mol%, the total amount of LiBr and MgBr2 added was 2.0 mol%, with a molar ratio of 1:1, and the amount of ammonium formate added was 1.0 mol.

[0058] S5: Preheat the substrate with the prepared composite interface passivation layer to 60°C, and then spin-coat the above perovskite precursor liquid onto the surface of the passivation layer. The spin-coating process is divided into two stages: the first stage is to homogenize the coating at a low speed of 1000 r / min for 10 s, and the second stage is to form a film at a high speed of 3000 r / min for 40 s; at the 25th second of the second stage of spin-coating, add 0.10 mL of anhydrous chlorobenzene as an anti-solvent to form a perovskite wet film.

[0059] S6: Perform a two-step annealing process on the perovskite wet film: first anneal at 60℃ for 2 min, then heat to 90℃ for 8 min, finally obtaining a quasi-two-dimensional blue light-emitting perovskite layer with a thickness of 45nm.

[0060] S7: A PO-T2T / TPBi composite electron transport layer with a mass ratio of 1:1 and a thickness of 30 nm is sequentially deposited on the surface of the light-emitting layer by vacuum evaporation, followed by a LiF electron injection layer with a thickness of 1 nm and an Ag metal cathode with a thickness of 100 nm. This completes the fabrication of the micro-display blue perovskite light-emitting diode.

[0061] Example 2

[0062] The difference between this embodiment and Example 1 is that, based on a total molar amount of PbBr2 and PbCl2 of 100 mol%, the amount of ammonium formate added is 0.5 mol%, the two-stage annealing conditions are the same as in Example 1, and the remaining steps and parameters are the same as in Example 1.

[0063] Example 3

[0064] The difference between this embodiment and Embodiment 1 is that a glass substrate with an ITO anode is used, and a hole injection layer, a TFB layer, a PTAA layer, and a composite interface passivation layer are prepared sequentially according to the method of Embodiment 1. Subsequently, a black photoresist compatible with the underlying material is applied to the surface of the composite interface passivation layer, and a pixel isolation barrier is formed by coating, pre-baking, exposure, development, and post-curing. The pixel isolation barrier has a height of 75nm, a linewidth of 3μm, and a pixel aperture size of 12μm.

[0065] A quasi-two-dimensional blue light perovskite precursor liquid with the same composition as in Example 1 and a solid content of 15 mg / mL was printed into the pixel opening using inkjet printing. The printing was carried out using a piezoelectric on-demand inkjet printhead with a nozzle orifice diameter of 10 μm, a single drop volume of 1 pL, and a droplet spacing of 10 μm. During printing, the substrate temperature was 50°C and the relative humidity of the printing environment was less than 18%.

[0066] After printing, the perovskite wet film undergoes a two-stage annealing process. The first stage annealing temperature is 60℃ for 2 minutes, and the second stage annealing temperature is 85℃ for 8 minutes to form a quasi-two-dimensional blue perovskite light-emitting layer. Subsequently, a PO-T2T / TPBi composite electron transport layer, a LiF electron injection layer, and an Ag metal cathode are sequentially vacuum-deposited to obtain a micro-display blue perovskite light-emitting diode with pixelated light-emitting areas.

[0067] Comparative Example 1

[0068] The difference between this comparative example and Example 1 is that ammonium formate is not added to the quasi-two-dimensional blue light perovskite precursor solution, but the same two-stage annealing treatment as in Example 1 is still used, and the remaining steps and parameters are the same as in Example 1.

[0069] Comparative Example 2

[0070] The difference between this comparative example and Example 1 is that ammonium formate is added to the quasi-two-dimensional blue light perovskite precursor solution, but the perovskite wet film is not subjected to two-stage annealing treatment, but instead is subjected to single-stage annealing treatment at 90°C for 8 minutes. The remaining steps and parameters are the same as in Example 1.

[0071] Comparative Example 3

[0072] The difference between this comparative example and Example 1 is that ammonium formate is not added to the quasi-two-dimensional blue light perovskite precursor solution, but PEABr is added as a control additive in the same molar amount as ammonium formate in Example 1; the amounts of PbBr2 and PbCl2 are adjusted accordingly so that the molar ratio of all Br elements and all Cl elements in the precursor solution is still 8:2, and the remaining steps and parameters are the same as in Example 1.

[0073] Comparative Example 4

[0074] The difference between this comparative example and Example 1 is that the 3-aminopropyltriethoxysilane / PEABr composite interface passivation layer is not set, and the quasi-two-dimensional blue perovskite emitting layer is directly formed on the surface of the PTAA layer. The remaining steps and parameters are the same as in Example 1.

[0075] Experimental Example 1

[0076] Electroluminescence performance tests were conducted on the devices obtained in Examples 1-3 and Comparative Examples 1-4. Five devices were randomly selected from each group. Before testing, the devices were placed in a nitrogen-protected environment for at least 30 minutes. A semiconductor parameter analyzer was used to apply voltage to the devices, and the current density, voltage, and brightness curves were recorded. A spectroradiometer was used to collect the electroluminescence spectra of the devices, and the emission peak position, full width at half maximum (FWHM), threshold voltage, maximum external quantum efficiency, and maximum brightness were calculated. The threshold voltage was defined as the brightness reaching 1 cd / m². 2 The corresponding voltmeter, and the current density, voltage, and brightness curves of Example 1 are as follows: Figure 2 As shown, the curves in Comparative Examples 1-3 are respectively as follows: Figures 3 to 5 As shown, the brightness and external quantum efficiency (EQE) comparison curves of each embodiment and the comparative example are as follows: Figure 6 As shown in the figure, the results are shown in Table 1.

[0077]

[0078] As shown in Table 1, all three examples achieved blue light emission with a relatively narrow full width at half maximum (FWHM). Compared to Comparative Example 1 without ammonium formate, Example 1 exhibited a lower turn-on voltage, higher maximum external quantum efficiency, and higher maximum brightness. This indicates that, under the same precursor system, the introduction of ammonium formate combined with a two-stage annealing process is beneficial for improving the crystallization process of the luminescent layer and the electroluminescence performance of the device. Compared to Comparative Example 2, Example 1 showed a lower turn-on voltage and higher device efficiency, indicating that the addition of ammonium formate requires a two-stage annealing process. If only ammonium formate is added and a single-stage annealing is used, its effect on initial crystallization regulation is limited. The subsequent residual control effect is insufficient; compared with Comparative Example 3, Example 1 has a lower turn-on voltage and higher electroluminescence efficiency when the emission peak positions are close, indicating that adding organic passivation components such as PEABr is not equivalent to the ammonium formate-assisted crystallization treatment of the present invention. This result shows that the treatment method of the present invention helps to form a synergy between defect regulation and carrier transfer; compared with Comparative Example 4, the device performance of Example 1 is better, indicating that the composite interface passivation layer has an auxiliary effect on reducing interface loss. This result shows that the crystallization regulation of the emission layer and the interface defect regulation jointly affect the device performance.

[0079] Experimental Example 2

[0080] The micro-display blue perovskite light-emitting diodes obtained in Examples 1-3 and Comparative Examples 1-4 were subjected to continuous lighting stability tests. Five devices were randomly selected from each group, and the effective light-emitting area of ​​each device was 4 mm². 2 After the device is fabricated, it is encapsulated in a nitrogen glove box using UV-curing adhesive and a cover glass. After encapsulation, it is left to stand in a nitrogen environment for no less than 30 minutes.

[0081] The test was conducted in a nitrogen atmosphere at 25±1℃, with both oxygen and water content not exceeding 0.1ppm. A constant current source was used to drive the devices, and a spectroradiometer was used to record the brightness and electroluminescence spectrum of the devices in real time. Before the test, the driving current of each device was adjusted to achieve an initial brightness L0 of 100 cd / m². 2 The initial current density was recorded, and then the driving current of each device was kept constant for 100 hours.

[0082] During the test, the brightness was recorded every 5 minutes from 0 to 1 hour, every 30 minutes from 1 to 10 hours, and every hour from 10 to 100 hours. Electroluminescence spectra were also collected at 0, 24, 48, 72 and 100 hours. The results are shown in Table 2.

[0083] The formula for calculating the luminance retention rate is as follows:

[0084]

[0085] Among them, R L The brightness retention rate is expressed as % (%) when the light is continuously lit up until time t. t This represents the brightness after continuous illumination up to time t, with units of cd / m². 2 L0 represents the initial brightness, which is 100 cd / m² in this experiment. 2 .

[0086] The formula for calculating the emission peak position shift is as follows:

[0087]

[0088] Where Δλ represents the emission peak position shift, in nm; λ t λ represents the electroluminescence peak position after continuous illumination up to time t, in nm; λ0 represents the initial electroluminescence peak position, in nm.

[0089]

[0090] As shown in Table 2, the initial brightness was 100 cd / m². 2Furthermore, under constant current driving conditions, the brightness decay rate of Examples 1-3 was lower than that of Comparative Examples 1-4. Specifically, the brightness retention rates of Example 1 after continuous lighting for 24h, 50h, and 100h were 95%, 90%, and 82%, respectively, and the emission peak shift after 100h was 2.1nm. Compared with Comparative Example 1, Example 1 showed higher brightness retention and smaller emission peak shift at each test time point, indicating that the combination of ammonium formate and two-stage annealing treatment is beneficial to improving the continuous lighting stability of the device. Compared with Comparative Example 2, Example 1 showed higher brightness retention under the same total annealing time, indicating that the staged annealing process has an impact on the crystal state of the light-emitting layer and the stability of continuous driving. Compared with Comparative Examples 3 and 4, the brightness decay and spectral shift of Example 1 were smaller, indicating that adding PEABr cannot replace ammonium formate to assist in crystallization treatment, and the composite interface passivation layer also has an auxiliary effect in reducing interface loss during continuous driving.

[0091] Experimental Example 3

[0092] The devices obtained in Example 1, Comparative Example 2 and Comparative Example 3 were tested for current density and voltage. The device was subjected to a gradually increasing positive voltage in a nitrogen atmosphere, and the current density at different voltages was recorded. The current density at 5V, the turn-on voltage and the maximum external quantum efficiency were selected as comparison indicators. The results are shown in Table 3.

[0093]

[0094] As shown in Table 3, Example 1 exhibits a higher current density and a lower turn-on voltage under the same test conditions, indicating that its carrier injection and transport resistance is relatively small. Comparative Example 2, which adds ammonium formate but does not employ two-stage annealing, has a lower current density than Example 1, indicating that ammonium formate is insufficient in its coordination with crystallization regulation and residue control under single-stage annealing conditions. Comparative Example 3, which undergoes organic passivation by adding PEABr, has a higher turn-on voltage and a lower current density, indicating that excessive organic components may affect carrier transfer.

[0095] Experiment Example 4

[0096] The device with pixel isolation barrier structure obtained in Example 3 was subjected to pixelated light emission test. During the test, the pixel array was lit up under the same driving conditions, 100 light-emitting pixels were randomly selected, and the emission peak position and brightness value of each pixel were recorded using a microspectral testing system, and the pixel brightness deviation was calculated. The device without pixel isolation barrier and prepared under the same inkjet printing conditions was used as a control sample. The results are shown in Table 4.

[0097]

[0098] As shown in Table 4, after setting the pixel isolation barrier, the quasi-two-dimensional blue light perovskite precursor liquid is mainly confined to the pixel opening area, the brightness deviation between pixels is reduced, and the light emission expansion phenomenon between adjacent pixels is reduced. This result shows that the pixel isolation barrier structure can provide film-forming boundaries for the micron-level light-emitting area, which is beneficial for the device of the present invention to adapt to the pixelation fabrication requirements of micro-displays.

[0099] Experimental Example 5

[0100] Using the quasi-two-dimensional blue light perovskite precursor solutions corresponding to Example 1 and Comparative Examples 1-3, thin films were prepared on quartz substrates under the same coating and annealing conditions. The photoluminescence quantum efficiency (PLQY) of the thin films was tested using the integrating sphere method with an excitation wavelength of 405 nm. The time-resolved photoluminescence (TRPL) decay curve was tested using the time-correlated single-photon counting method with an excitation wavelength of 405 nm. The detection wavelength was taken as the photoluminescence peak position of each sample. Three independent thin films were prepared for each group. The results are shown in Table 5. The time-resolved fluorescence decay curves were fitted using a double exponential decay model. The fitting formula is:

[0101]

[0102] Where I(t) represents the fluorescence intensity at a delay time of t; t represents the delay time after the excitation pulse ends, in ns; A1 and A2 represent the fitting factors of the first and second attenuation components, respectively; τ1 and τ2 represent the fluorescence lifetimes of the first and second attenuation components, respectively, in ns.

[0103] The average fluorescence lifetime is calculated using the following formula:

[0104]

[0105] Where, τ avg This represents the intensity-weighted average fluorescence lifetime, expressed in nanoseconds (ns).

[0106] Table 5. PLQY and TRPL test results of films obtained by different treatment methods

[0107]

[0108] As shown in Table 5, the PLQY of the film in Example 1 was 76.8%, and the average fluorescence lifetime was 41.6 ns, both higher than those of Comparative Examples 1-3. Comparative Example 1, without the addition of ammonium formate, had a PLQY of 48.7% and an average fluorescence lifetime of 20.4 ns. Comparative Example 2, although with the addition of ammonium formate, used single-stage annealing, had a PLQY of 61.9% and an average fluorescence lifetime of 29.8 ns. Comparative Example 3, through organic passivation with the addition of PEABr, had a PLQY of 56.3% and an average fluorescence lifetime of 25.7 ns. These results indicate that the combination of ammonium formate and two-stage annealing can reduce non-radiative recombination loss in the film and prolong the effective recombination lifetime of photogenerated carriers. Combined with the lower turn-on voltage and higher current density shown in Table 3, this indicates that the treatment method reduces defect recombination without hindering carrier transfer due to residual components or excessive organic components.

[0109] Experimental Example 6

[0110] X-ray diffraction tests were performed on the quasi-two-dimensional blue light perovskite thin films corresponding to Example 1 and Comparative Examples 1-3. Cu Kα rays were used for the test, with a scanning range of 2θ of 5°-50°, a step size of 0.02°, and a scanning rate of 2° / min. Peak fitting was performed on the low-n phase correlation diffraction peaks and the main phase diffraction peaks to calculate the proportion of the low-n phase peak area to the total characteristic peak area, and the half-width at half-maximum (WHM) of the main phase characteristic peaks was recorded. Three independent thin films were prepared for each group. The results in the table are the arithmetic mean, and the results are shown in Table 6.

[0111] Table 6. XRD test results of thin films obtained by different processing methods

[0112]

[0113] As shown in Table 6, the characteristic peaks of the main phase of each sample are all located at approximately 28.4° 2θ, with minimal changes in peak position, indicating that different treatment methods did not cause significant changes in the main crystal phase type. The full width at half maximum (FWHM) of the main phase peak in Example 1 is 0.184°, which is lower than that of Comparative Examples 1-3. The area ratio of its low n phase characteristic peak is 9.6%, which is also lower than that of Comparative Example 1 (24.1%), Comparative Example 2 (16.8%), and Comparative Example 3 (20.3%). The results indicate that the combination of ammonium formate and two-stage annealing is beneficial to improving the crystallization order of the main phase and making the crystal phase distribution of the quasi-two-dimensional perovskite relatively concentrated. Combined with the higher PLQY and longer average fluorescence lifetime in Table 4, it can be shown that the improvement in crystal phase distribution is consistent with the reduction in non-radiative recombination loss.

[0114] The technical scope of this invention is not limited to the content described above. Those skilled in the art can make various modifications and variations to the above embodiments without departing from the technical concept of this invention, and all such modifications and variations should fall within the protection scope of this invention.

Claims

1. A micro-display blue perovskite light-emitting diode, characterized in that, The device includes a substrate and an ITO anode disposed on one side of the substrate. Along the direction away from the substrate, a hole injection layer, a composite hole transport layer, a composite interface passivation layer, a quasi-two-dimensional blue perovskite emitting layer, a composite electron transport layer, an electron injection layer, and a metal cathode are sequentially stacked on one side of the ITO anode. The raw materials for preparing the quasi-two-dimensional blue perovskite emitting layer include CsBr, PbBr2, PbCl2, PEABr, TMABr, LiBr, MgBr2, and ammonium formate. Based on the total molar amount of PbBr2 and PbCl2 being 100 mol%, the amount of ammonium formate added is 0.2-3.0 mol.

2. The micro-display blue perovskite light-emitting diode according to claim 1, characterized in that: The ITO anode is an ITO transparent conductive film with a thickness of 120-150nm and a sheet resistance of 8-15Ω / sq.

3. The micro-display blue perovskite light-emitting diode according to claim 1, characterized in that: The hole injection layer is a PEDOT:PSS layer with a thickness of 25-35nm.

4. A micro-display blue perovskite light-emitting diode according to claim 1, characterized in that: The composite hole transport layer includes a TFB layer and a PTAA layer, wherein the thickness of the TFB layer is 15-25 nm and the thickness of the PTAA layer is 20-30 nm.

5. A micro-display blue perovskite light-emitting diode according to claim 1, characterized in that: The composite interface passivation layer is composed of 3-aminopropyltriethoxysilane and phenylethylammonium bromide in a mass ratio of 1.5:1-3:1, and the thickness of the composite interface passivation layer is 2-8 nm.

6. A micro-display blue perovskite light-emitting diode according to claim 1, characterized in that: The LiBr and MgBr2 are used as metal bromide dopants. Based on a total molar amount of 100 mol% for PbBr2 and PbCl2, the total molar amount of LiBr and MgBr2 is 0.5-5 mol.

7. A micro-display blue perovskite light-emitting diode according to claim 1, characterized in that: The composite electron transport layer is a blend of PO-T2T and TPBi, with a mass ratio of PO-T2T to TPBi of 1:1.2-1.2:

1. The thickness of the composite electron transport layer is 25-35 nm. The electron injection layer is a LiF layer with a thickness of 0.8-1.2 nm. The metal cathode is disposed on the side of the electron injection layer away from the quasi-two-dimensional blue perovskite emitting layer, and the metal cathode is an Ag layer with a thickness of 90-110 nm.

8. A method for fabricating a micro-display blue perovskite light-emitting diode as described in claims 1-7, characterized in that, Includes the following steps: S1: The substrate with mutually electrically isolated ITO pixel electrodes is cleaned and treated with ultraviolet ozone. PEDOT:PSS aqueous dispersion is spin-coated onto the surface of the ITO pixel electrode and then heat-treated to form a PEDOT:PSS hole injection layer with a thickness of 25-35nm. S2: A TFB layer and a PTAA layer are sequentially prepared on the hole injection layer; S3: Add 3-aminopropyltriethoxysilane and PEABr to isopropanol, mix evenly, spin coat onto the surface of the composite hole transport layer at a speed of 2000-4000 r / min, and then cure at 50-80℃ to form a composite interface passivation layer with a thickness of 2-8 nm. S4: Prepare a quasi-two-dimensional blue light perovskite precursor solution containing ammonium formate; S5: A pixel isolation barrier is formed on the surface of the composite interface passivation layer. The pixel isolation barrier forms a pixel opening that corresponds one-to-one with the ITO pixel electrode. The quasi-two-dimensional blue light perovskite precursor liquid is coated in multiple pixel openings to form perovskite wet films spaced apart from each other. S6: The perovskite wet film is subjected to a two-stage annealing process. The first stage annealing temperature is 50-70℃ and the time is 1-3 min. The second stage annealing temperature is 85-100℃ and the time is 5-10 min to obtain a quasi-two-dimensional blue light perovskite emitting layer. S7: A composite electron transport layer, an electron injection layer, and a metal cathode are sequentially fabricated on multiple quasi-two-dimensional blue light-emitting perovskite layers to form multiple blue light-emitting units disposed on the same substrate.

9. The method for fabricating a micro-display blue perovskite light-emitting diode according to claim 8, characterized in that: In step S5, when spin coating is used, the substrate preheating temperature is 55-70℃, including a first stage of low-speed homogenization and a second stage of high-speed film formation. The first stage has a rotation speed of 800-1200 r / min and a time of 8-12 s, and the second stage has a rotation speed of 2800-3500 r / min and a time of 30-45 s. During the 22nd-28th second of the second stage spin coating, 0.08-0.12 mL of anhydrous chlorobenzene is added as an anti-solvent.

10. An application of the blue perovskite light-emitting diode as described in any one of claims 1-8 as a blue light-emitting pixel or blue sub-pixel in a microdisplay device, characterized in that, The microdisplay device can be applied to near-eye displays, head-mounted displays, electronic viewfinders, micro-projection devices, or wearable display devices.

Citation Information

Patent Citations

  • Blue light perovskite film and blue light perovskite light emitting diode

    CN111048690A

  • Perovskite light-emitting diode with mixed cations and mixed anions and preparation method thereof

    CN111916572A